Efektivitas Pelaksanaan Peraturan Daerah Kabupaten Sumedang Nomor 1 Tahun 2023 Tentang Desa Wisata di Desa Karedok Kecamatan Jatigede Kabupaten Sumedang - Raynaldi, Rizki; Budiarto, Ruslan; Rahmafitria, Fitri (Media Wisata, 2024)
The development of tourist villages in Indonesia is currently showing quite a significant increase. The government has a role in establishing policies and regulations used as a guide for the development of tourism villages. Karedok Village is a tourist destination located in Jatigede District, Sumedang Regency. In 2023, the regional government of Sumedang Regency enacted regional rule Number 1 of 2023 regarding Tourism Villages to serve as a guideline for managing tourism villages. This research intends to evaluate the efficacy of applying these Regional Regulations in Karedok Village. The research methodology used is qualitative descriptive analysis. The discussion results indicate that the regulations in Karedok Village have not been implemented effectively. Causes include lack of collaboration among village institutions, limited community participation, ineffective tourism promotion, and lack of facilities and infrastructure. By establishing a solid and effective Tourism Village management, the purpose is to boost economic growth and achieve sustainable, community-based tourism in Karedok Village.